Clinical evaluation of freeze-dried secretome (lyosecretome) for osteoarthritis: a controlled trial in dogs and preliminary safety assessment in horses - Berni, Priscilla; Del Bue, Maurizio; Conti, Virna; Andreoli, Valentina; Ramoni, Roberto; Angelone, Mario; Squassino, Gian Paolo; Bari, Elia; Torre, Maria Luisa; Rinaldi, Maurizio; Dotti, Silvia; Rossi, Rossana; et al. (International journal of pharmaceutics, 2025)
[Display omitted] •A veterinary trial on dogs and horses with spontaneous osteoarthritis (OA) tested MSC-secretome efficacy.•MSC-secretome treatment showed no systemic adverse responses in dogs or horses.•In dogs, MSC-secretome improved lameness; mobility increased despite minimal pain reduction.•MSC-secretome proteins inhibit degradation, boost immunity, reduce inflammation, and support cartilage repair.•Findings support MSC-secretome benefits for OA and offer insights relevant to human OA due to similar pathophysiology. Most in vivo studies on MSC-secretome for osteoarthritis (OA) have relied on animal models, using products lacking pharmaceutical quality, not formulated for clinical use, and insufficiently characterized, limiting knowledge of its effectiveness. This study reports veterinary clinical trials on dogs and horses with spontaneous OA: in dogs (26 subjects), the trial is randomized, double-blinded, and controlled; in horses, 5 clinical cases were treated for safety assessment. Treatment consisted of hyaluronic acid with either lyosecretome – a freeze-dried, injectable MSC-secretome obtained through standardized GMP manufacturing – or mannitol, the lyosecretome excipient (control), intrarticularly administered. Patients underwent clinical evaluations and orthopedic assessments over an 80-day follow-up; dog-owner feedback was collected through questionnaires. Lyosecretome doesn’t induce systemic adverse responses. In dogs, improvement following treatment – significant in favor of lyosecretome – was observed, especially in reducing lameness; although it did not demonstrate significant pain reduction, patients were significantly more likely to walk, play, and move easily after exercise. Proteomic investigation supported these efficacy findings, revealing lyosecretome proteins involved in inhibiting protease and hyaluronidase, as well as in regulating immune response and inflammation, and those associated with cartilage regeneration and antioxidant activity. These results support the beneficial effect of MSC-secretome on joint disorders and offer insights that may be relevant to human patients, given the similarities in OA pathophysiology between humans and dogs or horses.